Resource allocation technique for Greener Cloud / Aiman Hilmi Abdul Azid - Abdul Azid, Aiman Hilmi (2017)
Cloud computing infrastructure are designed to support the accessibility and deployment of various service oriented applications by users. Cloud computing services are made available through the server firms or data centers. The complexity of the resource allocation increases with the size of the cloud infrastructure. This research present the performance of cloud in centralized and distributed cloud with using CloudSim. Result from both models tested were compared and analyzed.